PENGARUH SENAM ERGONOMIK TERHADAP TEKANAN DARAH PADA PRALANSIA HIPERTENSI DI WILAYAH KERJA PUSKESMAS KALISAT: The Effect of Ergonomic Gymnastics on Blood Pressure in Hypertensive Pre-elderly in the Working Area of Kalisat Health Center - Salsabila, Moch. Trifani; Widada, Wahyudi; Adi, Ginanjar Sasmito (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Hypertension is a medical condition that is often found in pre-elderly people and can lead to serious complications if not treated properly. Many pre-elderly people suffer from hypertension because as they age, blood vessels lose their elasticity so that blood pressure increases. One potential non-pharmacological method to lower blood pressure is ergonomic gymnastics. The purpose of this study is to determine the effect of ergonomic gymnastics on blood pressure in pre-elderly. The research method used is pre-experiment with One Group Pre-Test-Post-Test Design. Blood pressure measurements using a sphygmomanometer are recorded on the observation sheet. The sample was taken using a purposive sampling technique with a sample of 38 people. The results of the study showed that there was a decrease in blood pressure in the respondents with the results of the Wilcoxon test obtaining a p value of 0.000 <0.05 so that the H1 hypothesis decision was accepted. The conclusion obtained from the results of this study is that ergonomic gymnastics is effective in lowering blood pressure in elderly people with hypertension. Ergonomic gymnastics can be used as one of the non-pharmacological therapies to control blood pressure in elderly people with hypertension.